Effect of abietane diterpenes from Plectranthus grandidentatus on the growth of human cancer cell lines - Marques, CG (2015)
Five known abietane diterpenes, fatty acid esters of 7alpha-acyloxy-6beta-hydroxyroyleanone (1), grandidone A (2), 7alpha-acetoxy-6beta-hydroxyroyleanone (3), 6beta,7alpha-dihydroxyroyleanone (4), and coleon U (5), isolated from Plectranthus grandidentatus Gurke, were evaluated for their in vitro anti proliferative activity against five human cancer cell lines MCF-7, NCI-H460, SF-268, TK-10, and UACC-62. Coleon U (5) exhibited the strongest effect among all the assayed compounds. The abietane 3 revealed also a strong inhibitory effect while diterpenes 2 and 4 inhibited only slightly the growth of all cancer cell lines.